Evaluasi Pelatihan Non-Teknis Menggunakan Model Kirkpatrick: Systematic Literature Review 2016–2025 - Nicholas Brima Pradhika (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Training evaluation is a crucial component in assessing the effectiveness of human resource development programs, particularly non-technical training that emphasizes attitudes, behaviors, and values. This study aims to examine the application and effectiveness of the Kirkpatrick Four-Level Evaluation Model in the context of non-technical training through a Systematic Literature Review (SLR) approach. The research method employed an SLR based on the PRISMA guideline by analyzing 25 scholarly articles published between 2016 and 2025, obtained from both national and international databases. The results indicate that Level 1 (Reaction) and Level 2 (Learning) are the most dominantly applied evaluation levels, whereas the implementation of Level 3 (Behavior) and Level 4 (Results) remains relatively limited due to constraints in long-term observation and organizational data support. These findings confirm that the Kirkpatrick model remains relevant for evaluating non-technical training; however, it requires the strengthening of behavioral and results indicators to ensure that training impacts can be measured more comprehensively. This study provides practical implications for training providers in designing evaluations that are oriented toward behavioral change and medium-term impact.